Mathematical Tools for Cryptography: The Application of Laplace Transform in Cryptography and Its Advantages (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Information protection has been an important part of human life from ancient time. In computer field, information security becomes more and more important for humanity and new emerging technologies are developing in recent days. Cryptography is one of the most important techniques used for securing transmission of messages and protection of data in the present days. Which includes e-commerce electronic communications such as mobile communications, sending the emails business transactions which can be cash transaction or cashless transactions Pay-TV transmitting financial information security of ATM cards computer passwords etc, which includes on many aspects of our daily lives. Cryptography provides privacy and security for the secret information by hiding it. This can be done through mathematical technique. Laplace transform has many applications in various fields one such application is the cryptography. This technique uses a new iterative method for cryptography, in which can be applied successive Laplace transform of suitable function for encrypting the plain text and apply corresponding inverse Laplace transform for decryption. Generalization of the results is also obtained. Encryption by Laplace Transform is resistance to nearly all types of attacks on symmetric encryption algorithms. There is flexibility in implementation of algorithms. One can implement the algorithms as per the application demands. Which can find many application of encryption by Laplace Transform in banking, Security, One time password generation (OTP).